Inovasi Pendidikan Islam di Era Digital: Penguatan Nilai-Nilai Qurani bagi Generasi Masa Depan - Ibrahim, Basri (Program Pascasarjana IAIN Langsa, 2025)
The digital era has brought significant transformations across various aspects of life, including Islamic education. The rapid development of digital technologies, such as the internet, social media, and artificial intelligence, presents both challenges and opportunities in fostering a Quranic generation, namely individuals who uphold the Quran as a fundamental guide in their lives. However, scholarly discussions on how Islamic education can innovatively respond to digital transformation while preserving Quranic values remain limited. This study aims to analyze the urgency and forms of innovation in Islamic education in addressing the challenges of the digital era without compromising the essence of Quranic values. This research employs a qualitative method with a library-based approach, drawing on books, academic journals, and relevant scholarly sources related to Islamic education and digital transformation. The findings indicate that innovation in Islamic education encompasses the development of technology-based curricula, learning strategies, methods, and media, as well as contextual pedagogical approaches oriented toward character building and the internalization of Quranic values. Furthermore, teachers and Islamic educational institutions play a central role in integrating digital technology with spiritual and moral education. This study concludes that through appropriate and sustainable innovation, Islamic education can produce a generation that is not only digitally competent but also spiritually grounded, morally upright, and adaptable to contemporary challenges.